A CONTRASTIVE STUDY OF DEMONSTRATIVE PRONOUN IN ENGLISH AND JAPANESE - Ade Irma Suryani (Genta Mulia : Jurnal Ilmiah Pendidikan, 2014)
This article is a research report which consists of discussion of the various kinds, functions, and position of demonstrative pronouns in English and Japanese. In this article we would like to introduce what are the demonstrative pronoun in English and Japanese and also given the example of demonstrative pronoun in both of language. We also found some of contrastive study of demonstrative pronuon in English and Japanese. As seemingly simple and straightforward constructions, demonstratives are taught to foreign  language learners at a rather early stage in their language instruction.   For native speakers of Japanese,  English  this and that (singular), these and those (plural) seem fairly  easy to acquire, just  as the Japanese demonstratives ko-, so-, and a- seem like unproblematic  constructions for  native  speakers  of English.   However, language teachers often find  that even fairly  advanced learners of Japanese or English  have  trouble  with many of the less  transparent  issues  surrounding demonsrative usage. Key Words: Demonstrative pronoun, English, Japanese, and Contrastive study.